2004
DOI: 10.1158/1078-0432.ccr-1032-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 and Microsomal Prostaglandin E Synthase-1 Are Overexpressed in Squamous Cell Carcinoma of the Penis

Abstract: Purpose: Prostaglandin E 2 (PGE 2 ) promotes malignant growth. Cyclooxygenase (COX) catalyzes the synthesis of PGH 2 , which is converted, in turn, by microsomal prostaglandin E synthase (mPGES-1) to PGE 2 . One strategy for inhibiting carcinogenesis is to prevent PGE 2 production in premalignant and malignant tissues. It is important, therefore, to determine whether enzymes involved in PGE 2 biosynthesis are deregulated in neoplasia. The main purpose of this study was to determine whether amounts of COX-2 or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 54 publications
6
57
1
2
Order By: Relevance
“…Previous studies have shown that levels of COX-2 and PGE 2 are commonly increased in different tumor types (7 -19, 40 -43). Generally, the magnitude of these increases is quite variable both within and between tumor types (8,11,13,39). The current findings imply that intratumoral levels of COX-2 and prostanoids need to be interpreted in the context of whether cytotoxic therapy was given before tissue acquisition.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies have shown that levels of COX-2 and PGE 2 are commonly increased in different tumor types (7 -19, 40 -43). Generally, the magnitude of these increases is quite variable both within and between tumor types (8,11,13,39). The current findings imply that intratumoral levels of COX-2 and prostanoids need to be interpreted in the context of whether cytotoxic therapy was given before tissue acquisition.…”
Section: Discussionmentioning
confidence: 74%
“…This was carried out using methods that have been reported previously (39). Neutral buffered formalin-fixed tissue was embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…COX-2 is an enzyme with an imperative role in the metabolism of arachidonic acid, which leads to the production of prostaglandins, which in turn promote inflammation [32]. In fact, COX-2 is over-expressed in several malignancies, including cervical cancer [33][34][35][36][37]. As inflammation is known to contribute for cancer progression [31], COX-2 inhibition is expected to result in tumour growth inhibition whilst reducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Induction of mPGES-1 expression and its function have been observed in various diseases and systems in which COX-2-driven PGE 2 has been implicated, such as rheumatoid arthritis, febrile response, reproduction, bone metabolism, cardiovascular function, stroke and Alzheimer's disease (Kamei et al, 2004;Samuelsson et al, 2007;Hara et al, 2010). It has also been reported that mPGES-1 is constitutively expressed in several cancers, most of which also express COX-2 constitutively (Kamei et al, 2003;Golijanin et al, 2004). We have reported that the forcible transfection of mPGES-1 in combination with COX-2, but not with COX-1, into HEK293 cells led to cellular transformation, with a concomitant and robust increase in PGE 2 (Kamei et al, 2003).…”
Section: Introductionmentioning
confidence: 99%